Kontribusi Pendapatan Usaha Produksi Abon Ikan Tuna Terhadap Pendapatan Rumah Tangga (Studi Kasus Usaha Abon Ikan Tuna UMKM Bunda Kota Parepare) - Abbas Ramadhan M; Andi Sitti Halimah; Nurhaeda Nurhaeda (Universitas Muslim Maros, 2025)
This research investigates the role of Household Tuna Fish Floss Production Businesses in the fisheries sector in Indonesia, with a focus on Micro, Small, and Medium Enterprises (MSMEs) in the city of Parepare. The main objective of the study is to assess the income level generated from the tuna fish floss business and measure its direct contribution to household income. The research employs a purposive sampling approach with business owners and a production employee as respondents. The type of data used is quantitative, with primary data collected through observation and direct interviews, and secondary data from relevant literature. The study is conducted using a descriptive case study method, with data collection carried out through field research and literature reviews to support the analysis and findings. The results show that the average income from the Household Tuna Fish Floss Production Business of UMKM Bunda reaches Rp 5.782.323 per month. Furthermore, the direct contribution of this business to household income reaches 61%, indicating a significant economic impact on improving household welfare. These findings can become economic drivers at the micro level within the context of the national economy.